Quality of life of hypertensive patients visiting the Family Health Clinic, IIUM Kuantan - Abdul Razak, Nurul Syahirah; Abdul Hadi, Azwanis; Zainuddin, Norafiza (2020)
Hypertension is a chronic disease which significantly contributes to cardiovascular complications that could potentially affect a patient’s quality of life. The objective of this study is to measure the quality of life of hypertensive patients attending the Family Health Clinic at the International Islamic University Malaysia (FHC IIUM) and its associated factors. This cross sectional study adopted convenience sampling and was conducted through face to face interview of 106 hypertensive patients aged 18 and above using the WHOQOL-Bref questionnaire. Descriptive analysis, Mann Whitney U and Kruskal Walis test were used to measure the quality of life score and its association with sociodemographic factors. Our results showed that hypertensive patients have good quality of life with each domain’s median score ranged from 64.00 to 75.00. Age had significant association with quality of life in the environment domain with p=0.009 (p<0.05). Marital status also was significantly associated with quality of life in the social relationship domain with p=0.001 (p<0.05). Older age patient experienced better quality of life in the environment domain as compared with young and middle age patients. Married patients have better social relationship compared to single or widowed patients. This study concluded that there is significant association between quality of life of hypertensive patients and sociodemographic factors in environment and social relationship domains. Good quality of life among hypertensive patient is observed in this study.